Motor Skill Learning-Induced Functional Plasticity in the Primary Somatosensory Cortex: A Comparison Between Young and Older Adults - Predel, Claudia; Kaminski, Elisabeth; Hoff, Maike; Carius, Daniel; Villringer, Arno; Ragert, Patrick (Frontiers in Aging Neuroscience, 2020)
While in young adults (YA) the underlying neural mechanisms of motor learning are well studied, the involvement of the somatosensory system during motor skill learning in old adults (OA) remains sparse. Therefore, the aim of the present study was to investigate motor-learning induced neuroplasticity in the primary somatosensory cortex (S1) in YA and OA. Somatosensory evoked potentials (SEPs) were used to quantify somatosensory activation prior and immediately after motor skill learning in 20 right-handed healthy YA (age 19-35 years) and OA (age 57-76 years). Participants underwent a single session of a 30-minute co-contraction task of the abductor pollicis brevis (APB) and deltoid muscle. To assess the effect of motor learning, muscle onset asynchrony (MOA) between the onsets of the contractions of both muscles were measured using electromyography monitoring. In both groups, MOA shortened significantly during motor learning with YA showing bigger reductions. No changes were found in SEP amplitudes after motor learning in both groups. However, a correlation analysis revealed an association between baseline SEP amplitudes of the N20/P25 and N30 SEP component and the motor learning slope in YA such that higher amplitudes are related to higher learning. Hence, the present findings suggest that SEP amplitudes might serve as a predictor for the individual motor learning success, at least in YA. Additionally, our results suggest that OA are still capable of learning complex motor tasks showing the importance of motor training in higher age to remain an active part of our society as prevention from care dependency.